2013
DOI: 10.1016/j.aorn.2012.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing Documentation for Postoperative Nausea and Vomiting in the Electronic Health Record

Abstract: Postoperative nausea and vomiting (PONV) remains a common postoperative complication that causes patient discomfort and increases health care costs. Clinicians use the American Society of PeriAnesthesia Nurses (ASPAN) guideline to help prevent and treat PONV. However, the lack of standardized terminology in the electronic health record (EHR) and the lack of clinical decision support tools make it difficult for clinicians to document guideline implementation and to determine the effects of nursing care on PONV.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Besides the study design, the suspected incomplete documentation of smoking status and history of PONV might be considered as a problem. Compared with community prevalence of smoking status or PONV history our values seem to be too low for both parameters [ 6 , 42 , 43 ]. However, the imprecise documentation should not lead to systematic bias of effect estimates of any variable since the missing mechanism for smoking status and history of PONV should be completely at random.…”
Section: Discussionmentioning
confidence: 73%
“…Besides the study design, the suspected incomplete documentation of smoking status and history of PONV might be considered as a problem. Compared with community prevalence of smoking status or PONV history our values seem to be too low for both parameters [ 6 , 42 , 43 ]. However, the imprecise documentation should not lead to systematic bias of effect estimates of any variable since the missing mechanism for smoking status and history of PONV should be completely at random.…”
Section: Discussionmentioning
confidence: 73%
“…Fast-track programmes and day surgery have developed rapidly (Prabhakar, Cefalu, Rowe, Kaye, & Urman, 2017), highlighting the importance of an active approach before these patients return home. To detect patients with nausea, the use of patients' self-rated scores is recommended (Apfelbaum et al, 2013;DeBlieck et al, 2013). Frequent assessments of nausea are an important strategy to invite patients to participate in care.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate patients' recovery, that is, to relieve nausea-associated discomfort and medical risks, the use of patient-reported NRS scores may be just as applicable when communicating postoperative nausea as for pain. Furthermore, to meet the demand for documentation of symptom trajectories (DeBlieck et al, 2013;Gerbershagen et al, 2013;Saranto & Kinnunen, 2009), a daily summary of patients self-reported postoperative pain at rest and during activity were shown to be valid when assessments were frequent (Wikström et al, 2017). These results suggest that daily summaries of patients' self-reported postoperative nausea with the NRS are useful for evaluating postoperative nausea.…”
Section: Introduction and Backg Roundmentioning
confidence: 92%
See 2 more Smart Citations